Estudo da percepção dos clientes de serviços tecnológicos no setor eletroeletrônico brasileiro - Rocha, Ellen Debastiani da (2021)
Brazil is considered one of the 50 most entrepreneurial economies in the world according to the Global Entrepreneurship Research Association report (2019/20). And the services segment stands out for its intense use of technology, for the highest employability in the country, and for its representativeness in the economy of approximately 70% of the Gross Domestic Product. As a result of the innovation inserted in the commercial processes linked to the services and technologies produced in the electro-electronic sector, the market opportunity for specialized services, focused mainly on the areas of electrical energy, stands out. The renewable energy sources are in growing expansion, due to the increasingly accelerated development of technology, the improvement of living standards, and the continuous population growth in developing countries, which leads to an increase in energy demand. Given the complexity of this high-tech market, there is the challenge of reorganizing companies in a strategic way, where, besides price competition, a relationship and connections with service consumers must be built. Given this, it was identified the need to understand the customer's view of the service provided in the technological context of the Brazilian electro-electronic sector, which leads to the following problematic of this research: What are the important factors in the perception of customers for hiring technological services of tests on grid-connected photovoltaic inverters, performed in Brazil? And, thus, the objective of this study is to identify and understand the important factors of customer perception of technological testing services in grid-connected photovoltaic inverters, performed in Brazil. To this end, this study used a quantitative and qualitative approach, an applied nature, and an inductive method. First, a review of the bibliographic and systematic literature was conducted, seeking to identify the important factors in the perception of customers of technological services, as well as to situate the scenario of the electro-electronic and service sector, to understand the perception of service customers and the multicriteria support method for decision making to be used. The second step is the application stage of the research, through the collection instrument applied to companies contracting tests for certification of grid-connected photovoltaic inverters in Brazil. At this point the characterization of the respondents and the degree of importance attributed to each factor is analyzed, through the Analytic Hierarchy Process method. Finally, it was found which factors are important in the perception of customers of technological services for testing grid-connected photovoltaic inverters in Brazil for hiring services and how the market can use this information to strengthen its relationship with the customer.